Implementing A Lean Six Sigma–Based digital dashboard to improve cutting tool management in machining production - Dzulfikar Arifuddin; Gembong Baskoro; Filiana Santoso (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
Cutting tool management directly affects machining performance, production continuity, and inventory control in manufacturing systems. In many machining environments, particularly within Southeast Asian automotive component production, tool monitoring and decision-making remain dependent on manual records and fragmented data sources, leading to inconsistent replacement practices, inaccurate inventory levels, and limited process visibility. This study examines the implementation of a Lean Six Sigma–based digital dashboard to improve cutting tool management in a machining production line using the DMAIC (Define–Measure–Analyze–Improve–Control) framework. Data were collected through focus group discussions and questionnaires involving operators, engineers, and supervisors, while root causes were identified using fishbone analysis and Failure Mode and Effects Analysis (FMEA). Based on the analysis, a digital dashboard was developed to support real-time monitoring of tool usage, replacement activities, and inventory status. The results show measurable operational improvements, including a 27% reduction in tool replacement time, an increase in inventory accuracy from 82% to 96%, an 18% improvement in tool life, and a 23% reduction in downtime related to tool replacement. This study contributes to the literature by providing empirical evidence from an actual shop-floor implementation, demonstrating how the integration of Lean Six Sigma and digital dashboards can enhance operational control in machining production environments. The proposed approach is applicable to similar machining systems seeking improved efficiency and inventory performance.